+0  
 
0
173
3
avatar

http://prntscr.com/mvkqnp

 Mar 9, 2019
 #1
avatar+111394 
+1

f(-1)  =  -.25

f(1)  = -.50

 

Avg rate of change =

 

 [ f(1)  - f (-1) ]

___________   =

      1 - (-1) 

 

[ -.50  - (-.25) ]

____________   =

          2

 

-.25

_____   =

   2

 

-.125

 

 

cool cool  cool

 Mar 9, 2019
 #2
avatar
+1

how did you get this 

f(-1)  =  -.25

f(1)  = -.50

 Mar 9, 2019
 #3
avatar+111394 
0

Look at the graph....when x = - 1, then y = -1/4  = -.25

So f(x) =f (-1)  = -.25

 

Similarly.....when x = 1, then y = -1/2  =  -.50

So  ...f(1) =  -.50

 

cool cool cool

CPhill  Mar 9, 2019

16 Online Users

avatar
avatar
avatar